Marx generator GIN-1000 with 1 MV output voltage and 80 kJ stored energy - Avdeeva, A.V.; Basmanov, V.F.; Chistyakov, A.A.; Gordeev, V.S.; Gritsina, V.P.; Grishin, A.V.; Kalinychev, А.Е.; Karpov, G.V.; Kravchenko, М.Е.; Lomtev, S.S.; Nazarenko, S.T.; Nudikov, V.N.; et al. (Вопросы атомной науки и техники, 2006)
The results of development and study of Marx generator with output voltage of 1 MV and stored energy of 80 kJ are reported. The measured value of generator inductance is ~1.3 µH, the measured effective ohmic resistance ~ 1 Ohm.